A new freshwater pipefish species (Syngnathidae: Microphis) from the Sunda shelf islands, Indonesia - Haÿ, Vincent; Mennesson, Marion I.; Dahruddin, Hadi; Sauri, Sopian; Limmon, Gino; Wowor, Daisy; Hubert, Nicolas; Keith, Philippe; Lord, Clara (Zootaxa, 2024)
A new species of freshwater pipefish, Microphis arrakisae sp. nov., is described from the West Indonesian Islands (Java, Bali and Lombok). This species is morphologically very close to Microphis retzii (Bleeker, 1856), which is found in the eastern Indonesian Islands (Sulawesi, Ceram, Ambon and Papua). However, it can be distinguished by its in vivo coloration. Furthermore, genetic analysis of the partial COI gene (barcoding) indicates that it represents a distinct genetic lineage in the Indonesian region.